Inquisitive Logic Consequence and Inference in the Realm of Questions - Ciardelli, Ivano (Trends in Logic, Studia Logica Library,, 2022)
This open access book makes a case for extending logic beyond its traditional boundaries, to encompass not only statements but also also questions. The motivations for this extension are examined in detail. It is shown that important notions, including logical answerhood and dependency, emerge as facets of the fundamental notion of entailment once logic is extended to questions, and can therefore be treated with the logician's toolkit, including model-theoretic constructions and proof systems. After motivating the enterprise, the book describes how classical propositional and predicate logic can be made inquisitive-i.e., extended conservatively with questions-and what the resulting logics look like in terms of meta-theoretic properties and proof systems. Finally, the book discusses the tight connections between inquisitive logic and dependence logic.